PERLINDUNGAN HUKUM TERHADAP KEBOCORAN DATA PRIBADI KONSUMEN PENGGUNA FINANCIAL TECHNOLOGY CERMATI.COM - Naomi Carina (2021)
The phenomenome of a rapidly development of information technology has had a major influence on the pattern of human life. One of the advances in the financial sector nowadays is the adaptation of Financial Technology or Fintech. In August 2020, a financial technology platform from Indonesia, Cermati.com, has experienced a leak of its users' personal data. Personal data protection of Fintech consumers is regulated in the following laws: Law Number 8 of 1999 concerning Consumer Protection, Law, Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions, Government Regulation No. 71 of 2019 concerning the Implementation of Electronic Systems and Transactions, etc. However, the regulations are scattered and not comprehensive. The results and conclusions of this study are that regulations and protection related to personal data should be the main focus of the government in determining policy directions that are able to provide a sense of trust and comfort to consumers and financial industry players in Indonesia.